Fenomeni di transfer nell’italiano L3 di nederlandofoni: Conseguenze per la didattica - Badan, Linda; Cenni, Irene; Izzo, Giuliano (Incontri. Rivista europea di studi italiani, 2022)
Transfer phenomena in Italian L3 by Dutch-speaking learners Consequences for didactics The present study investigates some aspects of the learning process of Italian as an L3 by two groups of multilingual learners. In particular, through the examination of the learners’ cross-linguistic transfer occurrences we reflect on the didactic consequences of working with learners mastering several L2s. The results suggest that the learning process can be influenced by and adapted to the learners’ linguistic repertoire. Specifically, teachers can play an essential role facilitating the learning process of an L3: through actively promoting the development of metalinguistic awareness and metacognitive skills in their students, knowledge already acquired in other languages can be used to assist the learning of an L3.